The accuracy of placental alpha-microglobuline-1 test in diagnosis of premature rupture of the membranes - Maryam Khooshideh; Vida Radi; Reihaneh Hosseini; Ladan Hosseini (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Premature rupture of membranes (PROM) is a common obstetric issue during pregnancy which might lead to serious fetal or maternal problems. Therefore, an appropriate diagnosis and management of PROM are of significant importance in patients. Objective: The aim of this study was to determine the accuracy of placental alpha microglobuline-1 (PAMG-1) test in PROM diagnosis and compare this diagnostic method with other standard tests in diagnosis of PROM. Materials and Methods: In this prospective diagnostic accuracy study, patients with symptoms of membrane rupture in 16-39 weeks of gestation were involved. Three tests including Fern, Nitrazine and PAMG-1 were performed at the same time. Results: PROM was confirmed in 86 patients out of 100. The sensitivity and specificity were respectively 81.3% and 100% for Fern test, 93% and 92.8% for Nitrazine test, 98.9% and 92.8% for PAMG-1 test. PAMG-1 test showed higher sensitivity (98.9% with p<0.001) and accuracy (98%) compared with conventional tests. Although PAMG-1showed a lower positive predictive value (PPV) compared to conventional tests such as Fern test (100%), it was shown to be more accurate. Conclusion: The accuracy of PAMG-1 test was superior to both Fern and Nitrazine test in PROM diagnosis.